Spectrum of Hepatic Pathologies in Medicolegal Autopsies - Apoorva Nigam1 , Navneet Kaur2 , Ramesh Kumar Kundal3 , Akashdeep Aggrawal4 , Kanwardeep Kaur5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Silent liver disease is a major cause of morbidity and mortality in the population due to its silent progression to end stage liver disease without significant symptoms. We aim to study pattern of pathological findings and latent forms of diseases in the 100 liver autopsy specimen and to find clinicopathological correlation between clinical diagnosis and pathological diagnosis wherever possible. Method: The present study was conducted on 100 liver autopsy specimens received in the department of Pathology, Govt. Medical College, Patiala. Sections from representative areas were submitted for processing, sectioned and stained with Hematoxylin & Eosin stain. Results: Out of 100 specimens, 38 cases (38%) showed hepatic steatosis, followed by cirrhosis 14 cases(14%), chronic venous congestion 13 (13%) cases, portal triaditis 12 (12%) cases, normal 12 (12%) cases , hepatitis 8 (8%) cases , granulomatous/ tuberculosis pathology 2 (2%) cases and 1(1%)metastatic deposits of carcinoid tumour. Maximum cases seen in age group of 41-50 years with mean age 39.92±12.68 years. Liver disease predominated in males with male:female ratio of 6:1. Conclusion: Silent liver diseases are not uncommon. Autopsy examination of liver is very helpful to identify silent liver diseases like hepatic steatosis, cirrhosis, venous congestion and malignant tumours.